PENERAPAN METODE DEMONSTRASI DALAM PENGAJARAN NABI MUHAMMAD SAW. - M. Nur Salim; Iva Inayatul Ilahiyah (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2019)
Prophet Muhammad is a person whose entire aspects of life become role models for all mankind on earth, except for certain things that do apply specifically to him. The recording of the personality of the Prophet Muhammad that we inherited and preserved for his authenticity namely the Hadith is the most authoritative book to study his personality. From here we can trace how the method that was practiced by the Prophet Muhammad when teaching his friends. Instead the theory of education and teaching that is learned and applied in Indonesia is more likely to be adopted from theWest, due to victory in the second world war. Though the theory of education at that time only focused on meeting industrial and military needs. A method in the teaching process is very vital because it determines the level of effectiveness and efficiency of success in teaching itself. A teacher or educator is required to be careful in choosing methods so that success in teaching can be maximized. This paper seeks to reveal that the Demonstration method is a method often used by the Prophet Muhammad in his teaching. Because he had died, the source of the research data wascarried out through hadiths whose authenticity and validity had been selected by the hadith scholars.